A double‐blind, randomized, placebo‐controlled pilot trial of atorvastatin for nephrogenic diabetes insipidus in lithium users. (16th July 2020) - Fotso Soh, Jocelyn; Beaulieu, Serge; Trepiccione, Francesco; Linnaranta, Outi; Torres‐Platas, Gabriela; Platt, Robert W.; Renaud, Suzane; Su, Chien‐Lin; Mucsi, Istvan; D'Apolito, Luciano; Mulsant, Benoit H.; Levinson, Andrea; et al.
Abstract: Objective: Lithium remains an important treatment for mood disorders but is associated with kidney disease. Nephrogenic diabetes insipidus (NDI) is associated with up to 3‐fold risk of incident chronic kidney disease among lithium users. There are limited randomized controlled trials (RCT) for treatments of lithium‐induced NDI, and existing therapies can be poorly tolerated. Therefore, novel treatments are needed for lithium‐induced NDI. Method: We conducted a 12‐week double‐blind pilot RCT to assess the feasibility and efficacy of 20 mg/d atorvastatin vs placebo in the treatment of NDI in chronic lithium users. Patients, recruited between September 2017 and October 2018, were aged 18 to 85, currently on a stable dose of lithium, and determined to have NDI. Results: Urinary osmolality (UOsm) at 12 weeks adjusted for baseline was not statistically different between groups (+39.6 mOsm/kg [95% CI, −35.3, 114.5] in atorvastatin compared to placebo groups). Secondary outcomes of fluid intake and aquaporin‐2 excretions at 12 weeks adjusted for baseline were −0.13 L [95% CI, −0.54, 0.28] and 98.68 [95% CI, −190.34, 387.70], respectively. A moderate effect size was observed for improvements in baseline UOsm by ≥100 mOsm/kg at 12 weeks in patients who received atorvastatin compared to placebo (38.45% (10/26) vs 22.58% (7/31); Cohen's d = 0.66). Conclusion: Among lithium users with NDI, atorvastatin 20 mg/d did not significantly improve urinary osmolality compared to placebo over a 12‐week period. Larger confirmatory trials with longer follow‐up periods may help to further assess the effects of statins on NDI, especially within patients with more severe NDI.